A dry carbon fiber tape containing nanofiber film and a preparation method and application thereof

Dry carbon fiber ribbons prepared by electrospinning and hot pressing to produce nanofiber membranes solve the problems of complex processes and unstable performance in existing technologies, and realize the automated production of low-cost, high-performance carbon fiber ribbons, which are suitable for automated molding and manufacturing of composite materials.

CN120792193BActive Publication Date: 2026-11-03SHANGHAI AIRCRAFT MFG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510782361.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2026-11-03
Estimated Expiration
2045-06-12

AI Technical Summary

Technical Problem

The existing dry carbon fiber tape manufacturing process is complex, has unstable performance, and is costly, making it difficult to meet the needs of automated production and limiting its widespread application in the field of automated molding and manufacturing of composite materials.

Method used

Nanofiber membranes were prepared by electrospinning, and unidirectional carbon fibers were impregnated with a setting emulsion and then hot-pressed with a composite setting agent to form dry carbon fiber tapes containing nanofiber membranes, which simplified the process and improved performance stability.

Benefits of technology

The prepared dry carbon fiber tape has stable properties, can be stored at room temperature for several months, has a porosity of less than 0.5%, and excellent mechanical properties, making it suitable for automated laying processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005446089050000151
    Figure BDA0005446089050000151
  • Figure BDA0005446089050000161
    Figure BDA0005446089050000161
Patent Text Reader

Abstract

The present application relates to a kind of dry state carbon fiber tape containing nanofiber membrane and its preparation method and application.The preparation method includes the following steps: nanofiber membrane is prepared by thermoplastic resin A through electrospinning process;After being dipped in setting emulsion, dry to obtain the setting unidirectional carbon fiber tape;After the setting unidirectional carbon fiber tape is added with composite setting agent on both sides, it is carried out hot-pressing treatment with the nanofiber membrane, and the dry state carbon fiber tape containing nanofiber membrane is obtained.The preparation method is simple, and the production cost is low, and the dry state carbon fiber tape prepared by the preparation method has stable performance, and the product obtained when being applied to automatic placement process has porosity less than 0.5%, and excellent mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber-reinforced composite materials technology, and in particular to a dry carbon fiber tape containing a nanofiber membrane, its preparation method, and its application. Background Technology

[0002] Carbon fiber composites are increasingly used in aerospace and transportation structures due to their high specific strength, high specific modulus, wide range of material design flexibility, convenient integral molding capability, and excellent fatigue and corrosion resistance. To achieve cost-effective and efficient composite material manufacturing, automated production technology, especially automated layup technology, is crucial. However, current research in this field has not yet achieved the industrial production of dry fibers, limiting the development of automated molding and manufacturing of carbon fiber composites.

[0003] Currently, carbon fiber prepreg is the primary material suitable for automated fiber placement; however, the low-temperature storage of prepreg significantly increases the cost of composite materials. Therefore, exploring the preparation of dry carbon fiber tape has become a major development direction. Dry carbon fiber tape is not only easy to store and transport, but can also be directly applied to automated placement processes, greatly improving production efficiency and product precision. In particular, with the rapid development of automated fiber placement technology, its ability to precisely control the fiber bundle and adjust the amount of prepreg in real time perfectly meets the automated manufacturing needs of large-sized components with irregular shapes and complex boundaries, driving innovation in the manufacturing process of large and complex composite parts. However, most current research on dry carbon fiber tape preparation technology is still in the experimental and verification stage, making it difficult to meet the needs of industrial production.

[0004] Existing technologies such as CN106470825A and CN111251625A provide methods for preparing dry fiber tapes, but they suffer from problems such as complex processes, unstable performance, or high costs. These issues not only affect the product quality of dry carbon fiber tapes but also limit their widespread application in the field of automated molding and manufacturing of composite materials. Specifically, some traditional methods use adhesive materials and nonwoven coverings combined with carbon fibers to prepare dry fiber tapes. While this method offers strong design flexibility, the preparation process is relatively complex, and the performance stability is poor. Additionally, some methods utilize the viscous resin in prepregs to shape the carbon fibers. Although this can improve the performance of the product to some extent, the storage and preparation costs of the prepreg are high, and uneven coating can easily lead to uneven product thickness and poor stability.

[0005] Therefore, developing a simple, stable, and low-cost method for preparing dry carbon fiber tapes containing nanofiber membranes is of great significance for promoting the development of automated molding and manufacturing of carbon fiber composite materials. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a dry carbon fiber tape containing a nanofiber membrane, its preparation method, and its applications. The preparation method is simple and has low production costs. The dry carbon fiber tape prepared using this method exhibits stable performance, requires no refrigeration, can be stored at room temperature for several months, and when applied to an automated layup process, the resulting product has a porosity of less than 0.5% and excellent mechanical properties.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing a dry carbon fiber ribbon containing a nanofiber membrane, the method comprising the following steps:

[0009] Nanofiber membranes were prepared from thermoplastic resin A by electrospinning.

[0010] Unidirectional carbon fibers are impregnated with a sizing emulsion and then dried to obtain sizing unidirectional carbon fiber tapes.

[0011] The shaped unidirectional carbon fiber tape is hot-pressed with the nanofiber membrane after being added to both sides with a composite sizing agent. This yields the dry carbon fiber tape containing the nanofiber membrane.

[0012] This invention involves first impregnating and shaping unidirectional carbon fiber tape with a shaping emulsion to obtain a shaped unidirectional carbon fiber tape. Then, a composite shaping agent is added to both sides of the tape, followed by hot-pressing with a nanofiber membrane prepared by electrospinning to obtain a dry carbon fiber tape containing the nanofiber membrane. This preparation method is simple and has low production costs. The dry carbon fiber tape prepared by this method has stable properties, requires no refrigeration, and can be stored at room temperature for several months. When applied to automated layup processes, the resulting product has a porosity of less than 0.5% and excellent mechanical properties. This invention effectively solves the problems of complex processes and poor stability in current dry fiber tape preparation methods and is suitable for automated layup technology.

[0013] Nanofiber membranes prepared by electrospinning possess high specific surface area and a three-dimensional network structure, enabling them to uniformly fill the microscopic gaps between carbon fibers and form a continuous interface layer. This structure exhibits a physical anchoring effect with the carbon fiber surface during hot pressing, significantly reducing interlayer slippage, thereby lowering the porosity of the product (<0.5%) and improving its anti-delamination ability. The method of impregnating unidirectional carbon fibers with a setting emulsion followed by drying to obtain shaped unidirectional carbon fiber tapes effectively removes moisture while avoiding oxidative damage to the carbon fibers and retaining their tensile strength.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.

[0015] As a preferred embodiment of the present invention, the solid content of epoxy resin in the shaping emulsion is 1-2 wt%, for example, it can be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, or 2 wt%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0016] In this invention, the epoxy resin solid content in the setting emulsion is 1-2 wt%, which can play a good role in setting. If the content is too high, the porosity of the product obtained by the automatic laying process of the dry carbon fiber tape will increase, resulting in poor product permeability. If the content is too low, the dry fiber tape prepared will be loose, with poor stability, and reduced interlaminar shear strength and interlaminar fracture toughness.

[0017] It should be noted that the sizing emulsion in this invention is obtained by mixing epoxy resin, methyl methacrylate and an initiator. By adjusting the mass ratio of each raw material component, the solid content of epoxy resin in the obtained sizing emulsion reaches a suitable range, such as 1-2 wt%.

[0018] It should be noted that there are no special limitations on the type of initiator; commonly used initiators in the art are applicable, including but not limited to peroxide initiators. Based on a 100% mass percentage content of the emulsion, the mass percentage content of the initiator is 0.1-0.7%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, or 0.7%, as well as specific values ​​between these ranges. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0019] Preferably, the epoxy resin includes any one or a combination of at least two of bisphenol A type epoxy resin, phenylphenol modified epoxy resin, or polyurethane modified epoxy resin.

[0020] Preferably, the bisphenol A type epoxy resin includes E-51 epoxy resin and / or E-44 epoxy resin.

[0021] As a preferred embodiment of the present invention, the mass fraction of the composite sizing agent in the dry carbon fiber tape is 2-12%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0022] When the composite setting agent of the present invention has a mass fraction of 2-12% in the dry carbon fiber tape, the resulting dry fiber tape has suitable viscosity. The bonding layer (composed of the setting emulsion and the composite setting agent) effectively inhibits the slippage between fiber layers (between the set unidirectional carbon fiber tape and the nanofiber membrane) and prevents loosening and delamination. When the content of the composite setting agent is too low, the binder cannot form a continuous interface, the epoxy resin crosslinking density is insufficient, and the interlayer bonding strength decreases (the combined effect of interlayer shear strength and interlayer fracture toughness is reduced). When its content is too high, local accumulation between fibers hinders melt penetration during hot pressing, forming pores, which increases porosity. At the same time, it also increases the rigidity of the fiber tape, making it prone to wrinkles or breakage, thus reducing the interlayer fracture toughness.

[0023] Preferably, the composite setting agent is a solid particle at a temperature of 60-100℃ (e.g., 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃ or 100℃, etc.).

[0024] Preferably, the particle size of the composite setting agent is 10-50 μm, for example, it can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, as well as specific particle values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific particle values ​​included in the range.

[0025] Preferably, the softening point temperature of the composite setting agent is 120-200℃, for example, it can be 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃ or 200℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0026] As a preferred embodiment of the present invention, the composite setting agent comprises thermoplastic resin B and epoxy resin.

[0027] In this invention, when the composite shaping agent is thermoplastic resin B and epoxy resin, the two can work synergistically to improve the melt penetration and cross-linking effect of the composite shaping agent. As a result, the obtained dry carbon fiber tape maintains low porosity while also possessing excellent comprehensive properties such as high interlaminar shear strength and interlaminar fracture toughness.

[0028] In this invention, the epoxy resin may be, for example, E51 (epoxy equivalent 182-192 g / eq) from a tin resin factory or AG-80 (epoxy equivalent 110-125 g / eq) produced by Shanghai Huayi Resin Co., Ltd.

[0029] Preferably, the mass ratio of the thermoplastic resin B to the epoxy resin is 1:(1-3), wherein (1-3) can be, for example, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8 or 3, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0030] When the mass ratio of thermoplastic resin B to epoxy resin in this invention is 1:(1-3), the epoxy resin content in the composite setting agent is slightly higher than that of thermoplastic resin B. The resulting dry fiber tape has suitable viscosity and does not exhibit looseness or delamination. When the mass ratio is too low, the epoxy resin content is too high, leading to excessively high porosity in the product obtained during the automatic layup process, resulting in insufficient permeation. Conversely, when the mass ratio is too high, the epoxy resin content is too low, resulting in loose and unstable dry fiber tape. Furthermore, when the mass ratio is 1:2, the melt penetration and crosslinking reaction of the composite setting agent are optimally synergistic, with a porosity <0.5%.

[0031] As a preferred embodiment of the present invention, the thermoplastic resin A and thermoplastic resin B each independently comprise any one or a combination of at least two of polyethersulfone resin, polyetheretherketone, polyphenylene sulfide, polyimide, polyamide, polyamide, polypropylene, or polyethylene terephthalate.

[0032] In this invention, when polyethersulfone resin is selected as the thermoplastic resin B, it has better thermal stability and better compatibility with epoxy resin than other resins.

[0033] In this invention, the polyethersulfone resin (PES) can be, for example, polyethersulfone E6020P or PESU supplied by BASF AG, Germany. E2020P has a weight-average molecular weight of 55000 g / mol.

[0034] It should be noted that the thermoplastic resin B in the composite setting agent of this invention and the thermoplastic resin A, the raw material for preparing the nanofiber membrane, are the same type of thermoplastic resin, and they can be of the same or different weight-average molecular weight. Similarly, the epoxy resin in the setting emulsion and the epoxy resin in the setting emulsion are the same type of epoxy resin, and they can be of the same or different weight-average molecular weight.

[0035] Preferably, the concentration of the electrospinning solution in the electrospinning process is 8-15 wt%, for example, it can be 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0036] Preferably, the solvent of the electrospinning solution in the electrospinning process is N,N-dimethylformamide (DMF) and / or dimethylacetamide (DMAc).

[0037] Preferably, the receiving distance in the electrospinning process is 15-25cm (e.g., 15cm, 17cm, 19cm, 21cm, 23cm, or 25cm, etc.), the spinning voltage is 15-25kV (e.g., 15kV, 17kV, 19kV, 21kV, 23kV, or 25kV, etc.), and the spinning speed is 0.5-2mL / h (e.g., 0.5mL / h, 0.7mL / h, 1mL / h, 1.2mL / h, 1.4mL / h, 1.6mL / h, 1.8mL / h, or 2mL / h, etc.).

[0038] It should be noted that the spinning time in the electrospinning process of this invention is not specifically limited and can be adjusted according to the actual requirements of film thickness, for example, it can be 4-8 hours. Additionally, the ambient humidity in the electrospinning process of this invention is ≤30%.

[0039] This invention prepares nanofiber membranes via electrospinning, a simple process using a single material that allows for excellent stability control. Furthermore, the electrospinning process reduces the fiber diameter of the thermoplastic resin A, resulting in nanoscale fiber membranes. When the resulting dry carbon fiber tapes are applied in automated layup processes, the resulting products exhibit lower porosity and thus better mechanical properties. Compared to conventional polyethersulfone fiber mats, the nanofiber membranes prepared by this invention via electrospinning are thinner, more stable, suitable for complex component layup, and possess lower porosity and superior mechanical properties.

[0040] Preferably, the thickness of the nanofiber membrane is 20-80 μm, for example, it can be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm or 80 μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0041] Preferably, the basis weight of the nanofiber membrane is 2-15 g / m³. 2 For example, it can be 2g / m 2 4g / m 2 6g / m 2 8g / m 2 10g / m 2 12g / m 2 Or 15g / m 2 As well as the specific point values ​​between the above point values, due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values ​​included in the range.

[0042] As a preferred embodiment of the present invention, the unidirectional carbon fiber is obtained by continuous carbon fiber spinning.

[0043] This invention selects a method to prepare shaped unidirectional carbon fiber ribbons by impregnating unidirectional carbon fibers with a sizing emulsion. Capillary action allows the emulsion to fully penetrate the fiber bundle, forming a continuous and uniform resin coating with better storage stability and lower porosity. In contrast, the electrostatic fluidized bed method is prone to localized coating buildup due to airflow disturbances, and the electrostatic spraying method struggles to cover fiber gaps due to the random distribution of atomized particles. Furthermore, the impregnation method allows the epoxy resin emulsion to form a chemical bond with the carbon fiber surface, resulting in an interfacial shear strength of no less than 38 MPa, significantly higher than that of the electrostatic fluidized bed method and the electrostatic spraying method.

[0044] Preferably, the drying temperature is 80-120℃, for example, it can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃ or 120℃, and specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0045] Preferably, the drying time is 30-60 minutes, for example, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0046] Preferably, the thickness of the shaped unidirectional carbon fiber tape is 150-400μm, for example, it can be 150μm, 180μm, 200μm, 220μm, 250μm, 280μm, 300μm, 320μm, 350μm, 380μm or 400μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0047] As a preferred embodiment of the present invention, the composite setting agent is added by spreading.

[0048] Preferably, the temperature of the hot pressing treatment is 200-250℃, for example, it can be 200℃, 205℃, 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 245℃ or 250℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0049] Preferably, the pressure of the hot pressing treatment is 1-3 MPa, for example, it can be 1 MPa, 1.2 MPa, 1.4 MPa, 1.6 MPa, 1.8 MPa, 2.0 MPa, 2.2 MPa, 2.4 MPa, 2.6 MPa, 2.8 MPa or 3 MPa, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0050] Preferably, the hot pressing treatment time is 2-4 hours, for example, it can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0051] Preferably, the method for preparing the dry carbon fiber tape containing the nanofiber membrane specifically includes the following steps:

[0052] Thermoplastic resin A was prepared by electrospinning to obtain a thickness of 20-80 μm and a basis weight of 2-15 g / m. 2 Nanofiber membranes;

[0053] Continuous carbon fibers are spun into unidirectional carbon fibers, impregnated in a sizing emulsion with a solid content of 1-2 wt%, and dried at 80-120℃ to obtain a sizing unidirectional carbon fiber tape with a thickness of 150-400 μm.

[0054] After spreading the composite setting agent on both sides of the shaped unidirectional carbon fiber tape, the nanofiber membrane is attached to each side. Then, it is hot-pressed for 2-4 hours at a temperature of 200-250℃ and a pressure of 1-3MPa to obtain the dry carbon fiber tape containing the nanofiber membrane.

[0055] In a second aspect, the present invention provides a dry carbon fiber tape containing a nanofiber membrane prepared by the preparation method described in the first aspect.

[0056] Preferably, the thickness of the dry carbon fiber tape is 300-500μm, for example, it can be 300μm, 320μm, 350μm, 380μm, 400μm, 420μm, 450μm, 480μm or 500μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0057] Thirdly, the present invention provides an application of the dry carbon fiber tape containing a nanofiber membrane as described in the second aspect in the field of automated molding and manufacturing.

[0058] Compared with the prior art, the present invention has at least the following beneficial effects:

[0059] The present invention provides a simple and low-cost method for preparing dry carbon fiber tape containing nanofiber membranes. The resulting dry carbon fiber tape exhibits stable performance, requires no refrigeration, and can be stored at room temperature for up to 8 months. When applied to automated layup processes, the resulting products have a porosity of less than 0.5% and excellent mechanical properties. This method effectively solves the problems of complex processes and poor stability in current dry fiber tape preparation techniques and is suitable for automated layup technology. Detailed Implementation

[0060] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0061] Unless otherwise specified, all raw materials and reagents used in the following examples and comparative examples are commercially available. Some raw material information is as follows:

[0062] Polyethersulfone resin A: purchased from BASF, Germany E2020P;

[0063] Polyethersulfone resin B: Purchased from BASF, Germany, polyethersulfone E6020P;

[0064] Epoxy resin: purchased from Huachang Polymer Co., Ltd., MERICAN 3770;

[0065] Polyamide resin (PA): purchased from DuPont Zytel 101LNC010, USA;

[0066] Polyethylene terephthalate (PET): Purchased from China National Petroleum Corporation Liaoyang Petrochemical Company 80-K;

[0067] Continuous carbon fiber: UD, T700-24K from Toray Industries, Japan.

[0068] Setting emulsion: Epoxy resin and methyl methacrylate are mixed, and benzoyl peroxide is added as an initiator. By adjusting the mass ratio of epoxy resin to methyl methacrylate, the solid content of epoxy resin in the resulting setting emulsion is 0.5-3 wt%.

[0069] Example 1

[0070] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane, the preparation method of which includes the following steps:

[0071] Polyethersulfone resin A was prepared by electrospinning to obtain a thickness of 30 μm and a basis weight of 8 g / m. 2The polyethersulfone nanofiber membrane is described in the electrospinning process, wherein the electrospinning solution is a homogeneous polymer solution with a concentration of 12wt% formed by dissolving polyethersulfone resin A in dimethylacetamide (DMAc), the receiving distance is 20cm, the spinning voltage is 20kV, the spinning speed is 1mL / h, and the spinning time is 6h.

[0072] Continuous carbon fibers are spun into unidirectional carbon fibers and impregnated in a 2wt% shaping emulsion (i.e., epoxy resin solid content is 2wt% and initiator mass percentage is 0.2%). After drying at 100℃, a shaped unidirectional carbon fiber tape with a thickness of 300μm is obtained.

[0073] Composite shaping agent particles with a particle size of 20 μm, in a mass ratio of polyethersulfone resin B to epoxy resin of 1:1, are spread on both the upper and lower surfaces of the shaped unidirectional carbon fiber tape. The amount of composite shaping agent added is 5% of the total mass of the dry carbon fiber tape. Then, the polyethersulfone nanofiber membrane is attached to the upper and lower surfaces respectively. After that, it is hot-pressed for 2 hours at a temperature of 220°C and a pressure of 2 MPa to obtain a dry carbon fiber tape containing a nanofiber membrane with a thickness of 350 μm.

[0074] Example 2

[0075] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane, the preparation method of which includes the following steps:

[0076] Polyamide resin was prepared by electrospinning to obtain a thickness of 50 μm and a basis weight of 10 g / m. 2 The polyamide nanofiber membrane is described in the electrospinning process, wherein the electrospinning solution is a homogeneous polymer solution with a concentration of 8 wt% formed by dissolving polyamide in N,N-dimethylformamide (DMF), the receiving distance is 15 cm, the spinning voltage is 25 kV, the spinning speed is 0.5 mL / h, and the spinning time is 6 h.

[0077] Continuous carbon fibers are spun into unidirectional carbon fibers and impregnated in a 1 wt% shaping emulsion (i.e., epoxy resin solid content is 1 wt% and initiator mass percentage is 0.1%). After drying at 80℃, a shaped unidirectional carbon fiber tape with a thickness of 350 μm is obtained.

[0078] Composite shaping agent particles with a particle size of 30 μm, in a mass ratio of polyamide resin to epoxy resin of 1:2, are spread on both the upper and lower surfaces of the shaped unidirectional carbon fiber tape. The amount of composite shaping agent added is 8% of the total mass of the dry carbon fiber tape. Then, the polyamide nanofiber membrane is attached to the upper and lower surfaces respectively. After that, it is hot-pressed for 3 hours at a temperature of 200°C and a pressure of 3 MPa to obtain a dry carbon fiber tape with a thickness of 400 μm containing a nanofiber membrane.

[0079] Example 3

[0080] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane, the preparation method of which includes the following steps:

[0081] Polyethylene terephthalate was prepared by electrospinning to obtain a thickness of 80 μm and a basis weight of 15 g / m. 2 The polyethylene terephthalate nanofiber membrane is described in the electrospinning process, wherein the electrospinning solution is polyethylene terephthalate dissolved in dimethylacetamide (DMAc) to form a homogeneous polymer solution with a concentration of 15wt%, the receiving distance is 25cm, the spinning voltage is 15kV, the spinning speed is 2mL / h, and the spinning time is 6h.

[0082] Continuous carbon fibers are spun into unidirectional carbon fibers and impregnated in a 1.5 wt% shaping emulsion (i.e., epoxy resin solid content is 1.5 wt% and initiator mass percentage is 0.2%). After drying at 120℃, a shaped unidirectional carbon fiber tape with a thickness of 150 μm is obtained.

[0083] Composite sizing agent particles with a particle size of 50 μm, in a mass ratio of polyethylene terephthalate to epoxy resin of 1:3, are spread on both the upper and lower surfaces of the shaped unidirectional carbon fiber tape. The amount of composite sizing agent added is 8% of the total mass of the dry carbon fiber tape. Then, the polyethylene terephthalate nanofiber membrane is attached to the upper and lower surfaces respectively. After that, it is hot-pressed for 4 hours at a temperature of 220°C and a pressure of 1 MPa to obtain a dry carbon fiber tape containing a nanofiber membrane with a thickness of 300 μm.

[0084] Example 4

[0085] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the 2 wt% of the sizing emulsion (i.e., the epoxy resin solid content is 2 wt% and the initiator mass percentage is 0.2%) in Example 1 is replaced with 0.5 wt% of the sizing emulsion (i.e., the epoxy resin solid content is 0.5 wt% and the initiator mass percentage is 0.2%). All other raw materials, contents, and preparation methods are the same as in Example 1.

[0086] Example 5

[0087] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the 2 wt% of the setting emulsion (i.e., the epoxy resin solid content is 2 wt% and the initiator mass percentage is 0.2%) in Example 1 is replaced with 3 wt% of the setting emulsion (i.e., the epoxy resin solid content is 3 wt% and the initiator mass percentage is 0.2%). All other raw materials, contents, and preparation methods are the same as in Example 1.

[0088] Example 6

[0089] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the amount of composite sizing agent added in Example 1 is adjusted from 5% to 2% of the total mass of the dry carbon fiber tape. The other raw materials, contents and preparation methods are the same as in Example 1.

[0090] Example 7

[0091] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the amount of composite sizing agent added in Example 1 is adjusted from 5% to 12% of the total mass of the dry carbon fiber tape. All other raw materials, contents, and preparation methods are the same as in Example 1.

[0092] Example 8

[0093] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the amount of composite sizing agent added in Example 1 is adjusted from 5% to 1% of the total mass of the dry carbon fiber tape. All other raw materials, contents, and preparation methods are the same as in Example 1.

[0094] Example 9

[0095] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the amount of composite sizing agent added in Example 1 is adjusted from 5% to 14% of the total mass of the dry carbon fiber tape. All other raw materials, contents, and preparation methods are the same as in Example 1.

[0096] Example 10

[0097] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the composite sizing agent particles with a particle size of 20 μm in the mass ratio of polyethersulfone resin B to epoxy resin of 1:1 in Example 1 are adjusted to sizing agent particles with a particle size of 20 μm composed only of polyethersulfone resin B. The other raw materials, contents and preparation methods are the same as in Example 1.

[0098] Example 11

[0099] This embodiment provides a dry carbon fiber tape containing a nanofiber membrane. The only difference between this embodiment and Example 1 is that the composite sizing agent particles with a particle size of 20 μm in the mass ratio of polyethersulfone resin B to epoxy resin of 1:1 in Example 1 are changed to sizing agent particles with a particle size of 20 μm composed only of epoxy resin. All other raw materials, contents and preparation methods are the same as in Example 1.

[0100] Comparative Example 1

[0101] This comparative example provides a dry carbon fiber ribbon containing a nanofiber membrane, the preparation method of which includes the following steps:

[0102] Polyethersulfone resin A was melted at 290℃ and extruded into continuous fibers using a melt spinning machine. After the fibers were cooled and solidified by cooling rollers, they were collected into a loose fiber web. The fiber web was then laid flat in a mold and hot-pressed at 250℃ and 5MPa for 30 minutes in a hot press to partially melt and bond the fibers into a felt, ultimately yielding a product with a thickness of 300μm and a basis weight of 50g / m². 2 Polyethersulfone thermoplastic mesh.

[0103] Continuous carbon fibers are spun into unidirectional carbon fibers and impregnated in a 2wt% setting emulsion (i.e., epoxy resin solid content is 2wt%). After drying at 100℃, a 300μm thick shaped unidirectional carbon fiber tape is obtained.

[0104] Composite shaping agent particles with a particle size of 20 μm, in a mass ratio of polyethersulfone resin B to epoxy resin of 1:1, are spread on both the upper and lower surfaces of the shaped unidirectional carbon fiber tape. The amount of composite shaping agent added is 5% of the total mass of the dry carbon fiber tape. Then, the polyethersulfone thermoplastic mesh is attached to the upper and lower surfaces respectively. After that, it is hot-pressed for 2 hours at a temperature of 220°C and a pressure of 2 MPa to obtain a dry carbon fiber tape with a thickness of 700 μm containing a nanofiber membrane.

[0105] Comparative Example 2

[0106] This comparative example provides a dry carbon fiber ribbon containing a nanofiber membrane, the preparation method of which includes the following steps:

[0107] Polyethersulfone resin A was prepared by electrospinning to obtain a thickness of 30 μm and a basis weight of 8 g / m. 2 The polyethersulfone nanofiber membrane is described in the electrospinning process, wherein the electrospinning solution is a homogeneous polymer solution with a concentration of 12wt% formed by dissolving polyethersulfone resin A in dimethylacetamide (DMAc), the receiving distance is 20cm, the spinning voltage is 20kV, the spinning speed is 1mL / h, and the spinning time is 6h.

[0108] Continuous carbon fibers are unraveled into unidirectional carbon fibers, and epoxy resin powder sizing agent is deposited on the upper and lower surfaces of the unidirectional carbon fibers using an electrostatic spraying method to obtain a sizing unidirectional carbon fiber tape with a thickness of 300μm.

[0109] Composite shaping agent particles with a particle size of 20 μm, in a mass ratio of polyethersulfone resin B to epoxy resin of 1:1, are spread on both the upper and lower surfaces of the shaped unidirectional carbon fiber tape. The amount of composite shaping agent added is 5% of the total mass of the dry carbon fiber tape. Then, the polyethersulfone nanofiber membrane is attached to the upper and lower surfaces respectively. After that, it is hot-pressed for 2 hours at a temperature of 220°C and a pressure of 2 MPa to obtain a dry carbon fiber tape containing a nanofiber membrane with a thickness of 300 μm.

[0110] The dry carbon fiber tapes obtained in Examples 1-11 and Comparative Examples 1 and 2 were subjected to performance tests, and the test methods / standards are as follows:

[0111] (1) Stability test: The morphology of the dry carbon fiber tape was observed after being stored at 25°C for 8 months.

[0112] (2) Porosity: The porosity was analyzed by SEM;

[0113] (3) Interlaminar shear strength: The interlaminar shear strength was analyzed by short beam shear test (ASTM D2344);

[0114] (4) Interlaminar fracture toughness: The interlaminar fracture toughness was analyzed by end-notched bending specimens (ASTM D7905).

[0115] The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118]

[0119] The test results show that:

[0120] (1) As can be seen from Examples 1 to 11, the present invention designs a method for preparing dry carbon fiber tape, which results in dry carbon fiber tape with stable performance, no need for refrigeration, and can be stored at room temperature for 8 months without delamination. At the same time, it also has ultra-low porosity (<0.5%) and high mechanical properties (ILSS≥38MPa, GIC is 197.1-436.6J / m). 2 GIIC is 531.6-1073.2 J / m 2 It has excellent overall performance and technical effects.

[0121] (2) As can be seen from Examples 1, 4 and 5, the solid content of epoxy resin in the sizing emulsion of Example 4 is less than 1 wt%, and the interlaminar shear strength and interlaminar fracture toughness of the dry carbon fiber tape obtained therefrom are reduced. The solid content of epoxy resin in the sizing emulsion of Example 5 is higher than 2 wt%, and the porosity of the dry carbon fiber tape obtained therefrom is increased. This shows that by limiting the solid content of epoxy resin in the sizing emulsion, the present invention can further obtain dry carbon fiber tape with low porosity and high interlaminar bonding strength.

[0122] (3) As can be seen from Examples 6-9, the mass fraction of the composite sizing agent in the dry carbon fiber ribbon of Example 8 is less than 2%, and the interlaminar fracture toughness of the resulting dry carbon fiber ribbon is significantly lower than that of Examples 6 and 7; the mass fraction of the composite sizing agent in the dry carbon fiber ribbon of Example 9 is higher than 12%, and the porosity of the resulting dry carbon fiber ribbon is significantly higher than that of Examples 6 and 7. At the same time, its interlaminar fracture toughness is also significantly lower than that of Examples 6 and 7. This shows that by optimizing the mass fraction of the composite sizing agent in the dry carbon fiber ribbon, the present invention can enable the resulting dry carbon fiber ribbon to maintain a lower porosity while having better interlaminar bonding strength.

[0123] (4) By comparing Example 1 with Examples 10 and 11, it can be seen that in Examples 9 and 10, only a single resin sizing agent was used in the composite sizing agent, and the interlaminar fracture toughness of the dry carbon fiber tapes obtained by them decreased. Moreover, they could not maintain low porosity and high interlaminar shear strength at the same time. This shows that when the present invention uses a composite sizing agent composed of polyethersulfone and epoxy resin, the two can play a synergistic role, so that the dry carbon fiber tapes obtained can maintain low porosity while also having excellent comprehensive performance of high interlaminar shear strength and interlaminar fracture toughness.

[0124] (5) By comparing Example 1 with Comparative Example 1, it can be seen that the comparative document 1 uses polyethersulfone thermoplastic mesh (fiber felt), and the dry carbon fiber tape obtained by it has poor stability. It showed edge warping after 3 months of storage at room temperature, and its porosity was 34.8%, which was much higher than that of Example 1. At the same time, its interlaminar shear strength and interlaminar fracture toughness were also significantly reduced. This shows that the polyethersulfone nanofiber membrane obtained by the present invention through electrospinning process is thinner, more stable, suitable for complex component laying, and has lower porosity and better mechanical properties.

[0125] (6) By comparing Example 1 and Comparative Example 2, it can be seen that the unidirectional carbon fiber tape prepared by electrostatic spraying to deposit epoxy resin powder sizing agent has poor stability compared with the dry carbon fiber tape obtained by hot pressing the polyethersulfone nanofiber membrane prepared by electrospinning. After being stored at room temperature for 6 months, it showed slight delamination and its porosity was greater than 0.5%. The interlaminar shear strength and interlaminar fracture toughness were significantly worse. This shows that the unidirectional carbon fiber tape obtained by the present invention by using sizing emulsion impregnation and drying has better storage stability and lower porosity than the dry carbon fiber tape obtained by hot pressing the polyethersulfone nanofiber membrane prepared by electrospinning. It also has better mechanical properties.

[0126] In summary, this invention designs a method for preparing dry carbon fiber tape. The method involves first impregnating and shaping a unidirectional carbon fiber tape with a shaping emulsion to obtain a shaped unidirectional carbon fiber tape. Then, a composite shaping agent is added to both sides of the tape, followed by hot-pressing with a nanofiber membrane prepared by electrospinning. This method is simple, has low production costs, and produces dry carbon fiber tape with stable performance. It requires no refrigeration and can be stored at room temperature for 8 months without delamination. When applied to an automated layup process, the resulting product has a porosity of less than 0.5% and excellent mechanical properties.

[0127] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a dry carbon fiber tape containing a nanofiber membrane, characterized in that, The preparation method includes the following steps: Nanofiber membranes were prepared from thermoplastic resin A by electrospinning. Unidirectional carbon fibers are impregnated with a sizing emulsion and then dried to obtain sizing unidirectional carbon fiber tapes. The shaped unidirectional carbon fiber tape is hot-pressed with the nanofiber membrane after being added to both sides with a composite shaping agent to obtain the dry carbon fiber tape containing the nanofiber membrane. The epoxy resin in the sizing emulsion has a solid content of 1-2 wt%.

2. The preparation method according to claim 1, characterized in that, The epoxy resin includes any one or a combination of at least two of bisphenol A type epoxy resin, phenylphenol modified epoxy resin, or polyurethane modified epoxy resin.

3. The preparation method according to claim 1, characterized in that, The content of the composite sizing agent is 2-12% of the total mass of the dry carbon fiber tape.

4. The preparation method according to claim 3, characterized in that, The composite setting agent is a solid particle at a temperature of 60-100℃.

5. The preparation method according to claim 4, characterized in that, The particle size of the composite sizing agent is 10-50 μm.

6. The preparation method according to claim 4, characterized in that, The softening point temperature of the composite setting agent is 120-200℃.

7. The preparation method according to claim 6, characterized in that, The composite setting agent comprises thermoplastic resin B and epoxy resin.

8. The preparation method according to claim 7, characterized in that, The mass ratio of thermoplastic resin B to epoxy resin is 1:(1-3).

9. The preparation method according to any one of claims 1-8, characterized in that, Thermoplastic resin A and thermoplastic resin B each independently comprise any one or a combination of at least two of polyethersulfone resin, polyetheretherketone, polyphenylene sulfide, polyimide, polyamide, polypropylene, or polyethylene terephthalate.

10. The preparation method according to claim 1, characterized in that, The thickness of the nanofiber membrane is 20-80 μm.

11. The preparation method according to claim 10, characterized in that, The basis weight of the nanofiber membrane is 2-15 g / m³. 2 .

12. The preparation method according to claim 1, characterized in that, The unidirectional carbon fiber is obtained by spreading continuous carbon fiber yarn.

13. The preparation method according to claim 1, characterized in that, The drying temperature is 80-120℃.

14. The preparation method according to claim 13, characterized in that, The drying time is 30-60 minutes.

15. The preparation method according to claim 12, characterized in that, The thickness of the shaped unidirectional carbon fiber tape is 150-400 μm.

16. The preparation method according to claim 1, characterized in that, The composite setting agent is added by spreading.

17. The preparation method according to claim 1, characterized in that, The hot pressing temperature is 200-250℃.

18. The preparation method according to claim 17, characterized in that, The pressure for the hot pressing process is 1-3 MPa.

19. The preparation method according to claim 18, characterized in that, The hot pressing process takes 2-4 hours.

20. The preparation method according to any one of claims 1-19, characterized in that, The preparation method specifically includes the following steps: Thermoplastic resin A was prepared by electrospinning to obtain a thickness of 20-80 μm and a basis weight of 2-15 g / m. 2 Nanofiber membranes; Continuous carbon fibers are spun into unidirectional carbon fibers, impregnated in a sizing emulsion with a solid content of 1-2 wt%, and dried at 80-120℃ to obtain a sizing unidirectional carbon fiber tape with a thickness of 150-400 μm. After spreading the composite shaping agent on both sides of the shaped unidirectional carbon fiber tape, the nanofiber membrane is attached to each side. Then, it is hot-pressed for 2-4 hours at a temperature of 200-250℃ and a pressure of 1-3 MPa to obtain the dry carbon fiber tape containing the nanofiber membrane.

21. A dry carbon fiber tape containing a nanofiber membrane prepared by the preparation method according to any one of claims 1-20.

22. The dry carbon fiber tape according to claim 21, characterized in that, The thickness of the dry carbon fiber strip is 300-500 μm.

23. An application of the dry carbon fiber tape as described in claim 22 in the field of automated molding and manufacturing.

Citation Information

Patent Citations

  • Dry fibrous tape for manufacturing preform

    CN106470825A

  • Carbon fiber performing body and preparation process thereof

    CN111251625A

  • Preparation method of fiber reinforced composite material

    CN102173153A

  • Preparation method of fixed-width dry fiber band

    CN116728903A

  • Manufacturing method of dry fiber belt suitable for automatic laying liquid forming process

    CN117507411A